Mars entry guidance based on segmented guidance predictor–corrector algorithm. (December 2015) - Xia, Yuanqing; Shen, Ganghui; Zhou, Liuyu; Sun, Haoran
Abstract: The serious challenge of future Mars mission is to find an appropriate entry guidance algorithm that can deliver the lander to the desired parachute deployment site under highly uncertain initial conditions. This paper describes the development and evaluation of the common numerical predictor–corrector algorithm and gives an improved algorithm — segmented guidance predictor–corrector algorithm for the Mars entry guidance. The common predictor–corrector algorithm can be less sensitive to initial dispersions, but needs fast on-board computation. However, the improved predictor–corrector algorithm and lateral control logic, detailed descriptions in the paper, is provided to shorten the on-board computational time. Furthermore, a heading alignment guidance law is used to improve the horizontal accuracy of the vehicle at the end of entry phase. Simulation results show that this entry guidance algorithm demonstrates reliable and robust performance in situations with high uncertainties.